Legal Analysis of Criminal Liability of Physicians in Diagnostic Errors - A.Fachruddin; B.Kartawijaya (The Medical Journal of Hospital Management and Health Law, 2025)
Introduction: Diagnostic errors represent a critical intersection between medical practice and criminal law, challenging the boundaries of professional judgment and legal accountability. In Indonesia, the legal framework balancing a physician's professional autonomy with patient protection remains highly contested, particularly regarding when a medical misstep transitions from an civil error or ethical breach into criminal negligence. Methods: This study employs a normative legal research method (metode penelitian yuridis normatif), analyzing statutory frameworks, medical jurisprudence, and authoritative legal doctrines to evaluate the parameters of criminal liability. Results: The findings indicate that criminal liability for a diagnostic error cannot be automatically applied; it strictly requires the presence of gross negligence (culpa lata) that violates established medical standards, directly resulting in severe injury or death. Minor errors or misdiagnoses resulting from atypical disease presentations are shielded by the principle of medical judgment, provided the physician followed standard diagnostic protocols. Discussion: The discussion synthesizes statutory provisions with judicial precedents, evaluating the mens rea (guilty mind) required for criminal convictions. It contrasts ethical misconduct with criminal negligence and highlights a persistent research gap in defining clear objective criteria for culpa lata in complex medical procedures. Conclusions: This study concludes that a clear, standardized legal boundary is essential to prevent defensive medicine while upholding patient rights. It recommends the establishment of specialized medical-legal panels to provide objective assessments before criminal charges are pursued.